Polymerization shrinkage evaluation of three packable composite resins using a gas pycnometer (Pesquisa Odontológica Brasileira, 2003)
Modern restorative dentistry has been playing an outstanding role lately since composite resins, allied to adhesive systems, have been widely applied on anterior and posterior teeth restorations. The evolution of composite resins has mostly been verified due to the improvement of their aesthetic behavior and the increase in their compressive and abrasive strengths. In spite of these developments, the polymerization shrinkage inherent to the material has been a major deficiency that, so far, has been impossible to avoid. Using a gas pycnometry, this research investigated the polymerization shrinkage of three packable composite resins: Filtek P60 (3M), Prodigy Condensable (Kerr), and SureFil (Dentsply/Caulk), varying the distance from the light source to the surface of the resins (2 mm or 10 mm). The pycnometer Accupyc 1330 (Micromeritics, USA) precisely records helium displacement, allowing fast and reliable measurements of the volume of composite resin immediately before and after polymerization, without interference of temperature or humidity. Results were not found to be statistically different for the three tested resins, either for 2 mm or 10 mm-distance from the light source to the composite surface.